POLLINATION POWER - Angel, Heather; Royal Botanic Gardens, Kew (Chicago, IL : University of Chicago Press, 2015)
"From the wings of moths to the feet of hoverflies and the head feathers of nectar-seeking birds, the process of pollination is a natural marvel. How do the many annuals and perennials and shrubs and trees that populate the globe manage to lure the aid of bees and butterflies and other creatures at exactly the appropriate time? Pollination Power offers a unique, truly bird s-eye view of the wonders of pollination at work. In stunning full-color images, employing the latest photographic techniques, esteemed photographer Heather Angel has captures the intimate interactions of plants with their floral pollinators. The plants come not only from Angel s Surrey backyard and the Royal Botanic Garden at Kew, but from twenty countries where Angel has travelled from the rich floral kingdoms of the Cape of South Africa to the diversity of China and the Americas. The photos illustrate the varied techniques that flowers use to communicate with their pollinators. Some, for example, change color when the flower no longer has rewards to offer. Others control precisely when pollinators enter or leave by timing when they open and close their petals or when they emit a scent. This fascinating array of pollination repertoires crossfertilizes Angel s photos with a descriptive text. Featuring both common and exotic plants and temperate and tropical floral, Pollination Power will entice anyone with a passion for botanicals, from gardeners to botanists alike."--Publisher's website.
Includes bibliographical references and index.
Keywords: Pollination; Pollination by insects; Pollination by animals